The deregulation of quarterly reporting and its effects on information asymmetry and firm value - Vanessa Behrmann; Lars Hornuf; Daniel Vrankar; Jochen Zimmermann (Review of Quantitative Finance and Accounting, 2024)
In this article, we investigate accounting deregulation and analyze whether a reduction in the minimum content requirements for quarterly reporting negatively impacts information asymmetry and reduces firm value. Taking advantage of one of the rare deregulating measures, namely the transposition of the EU's Transparency Directive into German law, and using a novel dataset of firms listed on the Frankfurt Stock Exchange, we manually examine firms' quarterly reports for their content elements and construct a new quarterly reporting measure with an ordinal quality dimension. The results show that deregulation reverses beneficial regulatory effects and, on average, increases information asymmetry and decreases firm value. We find that this effect is stronger for first-tier stocks, highlighting the importance of quarterly reporting for these firms. The results are robust to potential selection effects regarding firms' choice of quarterly reporting content levels.
Keywords: G14; G32; 330; Quarterly reporting; Disclosure deregulation; Financial reporting; Interim management statement; Transparency directive